2020
DOI: 10.1186/s12864-020-06932-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide scan for common variants associated with intramuscular fat and moisture content in rainbow trout

Abstract: Background: Genetic improvement of fillet quality attributes is a priority of the aquaculture industry. Muscle composition impacts quality attributes such as flavor, appearance, texture, and juiciness. Fat and moisture make up about~80% of the tissue weight. The genetic architecture underlying the fat and moisture content of the muscle is still to be fully explored in fish. A 50 K gene transcribed SNP chip was used for genotyping 789 fish with available phenotypic data for fat and moisture content. Genotyped f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 132 publications
(199 reference statements)
1
4
0
Order By: Relevance
“…In this study, we identified new QTLs associated with production and flesh-quality traits in rainbow trout. However, our work is consistent with previous reports ( Gonzalez-Pena et al, 2016 ; Salem et al, 2018 ; Ali et al, 2020a ) in characterising the vast majority of these traits as polygenic.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, we identified new QTLs associated with production and flesh-quality traits in rainbow trout. However, our work is consistent with previous reports ( Gonzalez-Pena et al, 2016 ; Salem et al, 2018 ; Ali et al, 2020a ) in characterising the vast majority of these traits as polygenic.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, an older study detected QTLs for body weight and condition factor on linkage groups RT-9 (corresponding to Omy12) and RT-27 (corresponding to Omy2) ( Wringe et al, 2010 ). More recently, QTLs for muscle fat and moisture content were identified on chromosomes 19 and 29 in rainbow trout ( Ali et al, 2019 , 2020a ). In farmed Atlantic salmon, significant QTLs were identified on chromosomes 13, 18, and 20 with effects on growth and yield-related traits ( Tsai et al, 2015 ) and on chromosome 9 and 10 for fat content ( Sodeland et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no study reported a relationship between the three genes and TSCS. The gene ABCC9 harbors the most significant SNPs for production traits [ 41 ], the gene WDR7 is associated with sperm motility and concentration in Holstein-Friesian bulls [ 52 ], and the gene TXNL1 has an effect on moisture content in rainbow trout [ 53 ]. The response to oxygen-containing compound and the G-proteifan-coupled receptors signaling pathway were significantly detected based on all candidate genes for main effects.…”
Section: Resultsmentioning
confidence: 99%
“…GWA studies take advantage of linkage disequilibrium between SNP markers and genetic loci controlling a trait of interest. GWA studies have been conducted in the rainbow trout breeding program at the National Center for Cool- and Cold-Water Aquaculture (NCCCWA) for growth [ 6 ], muscle yield [ 7 ], intramuscular fat [ 8 ], fillet firmness [ 9 ], and disease resistance [ 10 ]. Another essential trait that requires attention is the fillet color—targeted in this study.…”
Section: Introductionmentioning
confidence: 99%